The occurrence of Anisakis larvae on hairtail, Trichiurus lepturus caught from the Pangandaran Waters, West Java, Indonesia - NISA QUROTA AYUN; LUTFI SEPTIANA DEWI; MURWANTOKO MURWANTOKO; Eko Setyobudi (Society for Indonesian Biodiversity, 2021)
Abstract. Ayun NQ, Dewi LS, Murwantoko, Setyobudi E. 2021. The occurrence of Anisakis larvae on hairtail, Trichiurus lepturus caught from the Pangandaran Waters, West Java, Indonesia. Biodiversitas 22: 1378-1384. This study aimed to investigate the prevalence, mean intensity, and type of Anisakis larvae infecting hairtail (Trichiurus lepturus) caught at Pangandaran Waters, West Java, Indonesia. It was conducted using 869 samples sourced from local fishermen. The parameters measured were the total length and weight of each T. lepturus. Furthermore, parasitological examination was carried out to investigate the occurrence of Anisakis larvae in the fishes. The selected samples of Anisakis were identified through morphological and molecular analysis. The results showed that the larvae were found either free in the abdominal cavity of the fishes or coiled and attached to the serosal layer of the gastrointestinal tract, gonad, liver, and muscle. The results showed that the larvae were found either free in the abdominal cavity of the fishes or coiled and attached to the serosal layer of the gastrointestinal tract, gonad, liver, and muscle. It also showed that their prevalence in the T. lepturus was at a moderate level (45.5%), with the mean intensity at 4.4 larvae/fish. Moreover, the larvae were mostly in the abdominal cavity (89%), as only a few were found in another part of the fishes. Morphological identification showed that the type of Anisakis present was type I, as they were characterized by the presence of mucron and ventriculus without caecum. Molecular analysis was carried out by sequencing the ITS region, and it confirmed that the nematode was Anisakis typica, a non-zoonotic parasite. These parasites were not present in the edible portion/muscle of the fishes, and had a relatively moderate prevalence and low intensity. Therefore, their presence posed a relatively low risk to human health. However, due to consumption patterns and the increasing popularity of seafood, being served raw or undercooked, the incidence of anisakiasis may increase in the future. In the other hand, the presence of these larvae might be used as a biological indicator for several ecological studies.